Kajian Al-Qur'an di Tatar Sunda Sebuah Penelusuran Awal - Jajang A. Rohmana (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
The commentary of the Qur'an in Sundanese since the beginning of the 20th century has helped strengthen the indigenization of the teachings of the Qur'an to the Islamic tradition in Sunda Island. It reflects the religious experience of the Sundanese people in interacting with their holy book and in the Sundaness natural environment. This study tries to explore the development of the study of the Qur'an in Sunda (West Java). This study is focused on the publication of the translations and the interpretations of the Sundanese throughout the late of the 19th century to the present time. The study seeks to prove that the development of the study of the Qur'an in Sunda Island reflects the strong influence of Islam which is reflected in the appreciation to its main sources. The study shows that the teaching of Islam is not only on the surface, but has become part of Islamic identity in Sunda. Keysword: Qur'anic study, Sunda Language, translation.